Deconstruction Overflowed: Doing Undoing from Philosophy's Outer Edge - Briggs, Robert (2023)
This article seeks to characterize deconstruction (and “theory” generally) as a practical activity in order to assess its potential effects in view of Marx’s 11th Thesis on Feuerbach. Taking its cue from Derrida’s reference to the “inner edge of philosophy” in Theory and Practice, the article juxtaposes Derrida’s ostensibly philosophical approach with the contentious, historiographic approach taken by Ian Hunter. Reflecting on the activity of deconstruction from the outer edge of philosophy, as it were, the discussion first reviews Derrida’s diagnosis of the philosophical impulse to monopolize authority over all theory and practice, then interprets this move via Hunter’s “empirical” attempt to situate and analyze different modes of philosophizing as concrete exercises in self-problematization. The discussion highlights the surprising convergences in Derrida’s and Hunter’s arguments before adopting this view from the outer edge of philosophy in order to reassess where and how deconstruction’s practical effects may be registered.